A proof‐of‐principle bite force study using two experimental test denture adhesives and a currently marketed denture adhesive - Mounir Atassi; Martin R. Ling; Kathy Oneglia; Thomas S. Dilauro (Wiley, 2020)
Abstract Objectives This proof‐of‐principle, single‐center, randomized, examiner‐blind, crossover study compared two experimental polyvinyl acetate (PVA)‐based denture adhesives (Test Adhesives 1 and 2) with a marketed reference polymethyl vinyl ether/maleic anhydride (PMV/MA)‐based adhesive and no adhesive using incisal bite force area over baseline over 12 hr (AOB0-12) in participants with an at least moderately well‐fitting complete maxillary denture. Previous in vitro studies suggested the experimental denture adhesives provided superior performance. Materials and Methods Participants were randomized to a treatment sequence such that each received each treatment once. Prior to treatment application (baseline) and at 0.5, 1, 3, 6, 9, and 12 hr following the application, participants bit on a force transducer until their maxillary denture dislodged. Between‐treatment differences in AOB0-12 were analyzed using analysis of covariance. For study validity, the reference adhesive was compared with no adhesive. Participants were asked to rate sensory experiences and ease of denture removal. Results Twenty‐three participants were included in the modified intent‐to‐treat population. Although Test Adhesives 1 and 2 had a higher mean AOB0-12 than no adhesive, differences were not statistically significant. No statistically significant difference was also found between the reference adhesive and no adhesive; hence, study validity was not attained. Participants did not report any clear differences between the test or reference adhesives in terms of taste or feel; however, dentures were easier to remove with the test adhesives versus reference. No treatment‐related adverse events were reported. Conclusion Neither the experimental PVA‐based denture adhesives nor the PMV/MA‐based reference product demonstrated a statistically significant difference in incisal bite force AOB0‐12 compared with no adhesive. The reasons for these unexpected results is unclear; they suggest that findings of in vitro tests for denture adhesive performance are not always translated to in vivo performance (Clinicaltrials.gov: NCT02937870).